The disparate impact of COVID-19 on the mental health of female and male caregivers. (April 2021) - Wade, Mark; Prime, Heather; Johnson, Dylan; May, Shealyn S.; Jenkins, Jennifer M.; Browne, Dillon T.
Abstract: Caregiver mental health is crucial to the wellbeing of children. This is most apparent when caregivers face high levels of stress or life adversity. To study this phenomenon in the current global context, this study examined the relation between stress/disruption from the COVID-19 pandemic and the mental health of female and male caregivers. Pre-pandemic childhood adversity was considered as a moderator of this association. A multi-national sample (United Kingdom, 76%; United States, 19%; Canada, 4%, and Australia, 1%) was recruited in May 2020, of whom 348 female and 143 male caregivers of 5–18 year-old children provided data on the constructs of interest. At this time, caregivers reported on their history of adverse childhood experiences (ACEs) and COVID stress/disruption. About two months later (July 2020) caregiver mental health was evaluated. We examined differences between female and male caregivers on ACEs, COVID stress/disruption, and mental health (distress, anxiety, substance use, and posttraumatic stress). Main and interactive effects of ACEs and COVID stress/disruption on each mental health outcome were examined. Female caregivers reported higher COVID stress/disruption, more ACEs, and greater distress, anxiety, and posttraumatic stress symptoms compared to male caregivers. Among female caregivers, higher COVID stress/disruption and more adverse childhood experiences (ACEs) independently predicted all mental health outcomes, consistent with a stress accumulation model. Among male caregivers, a pattern of interactions between COVID stress/disruption and ACEs suggested that the effects of COVID stress/disruption on mental health was stronger for those with higher ACEs, especially for substance use, consistent with a stress sensitization model. Higher levels of stress and mental health difficulties among female caregivers suggests a disproportionate burden due to pandemic-related disruption compared to male caregivers. Findings speak to the disparate effects of COVID-19 on the mental health of female compared to male caregivers, and the role of pre-existing vulnerabilities in shaping current adaptation. Highlights: Cross-national sample of caregiver mental health and COVID-19 stress/disruption. Compared to male caregivers, female caregivers report more COVID stress/disruption. Female caregivers report higher distress, anxiety, and posttraumatic stress. For female caregivers, COVID stress and ACEs independently predict mental health. For male caregivers, COVID stress and ACEs interact to predict mental health.